(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Traditionally, Public-Private Partnerships(PPPs) are known to contribute to infrastructure development in diverse socio-economic sectors. It is a misconstruction that PPPs are streamlined to a single functioning of developing and improving infrastructure yet this strategy can be adopted to integrate PPP for sustainable skills development in Technical and Vocational Education and Training (TVET) with a view of responding to the labour market demand realities. Using a mixed methods approach the study sought to establish the feasibility of PPPs for sustainable skills development in TVET by soliciting data from institutions of higher learning and industry. A simple random sampling of 5 TVET institutions and 10 lecturers,5 administrators, and 5 captains of industry were purposively sampled to respond and participate in the study respectively. The data were descriptively and thematically analyzed for a balanced view of the findings. The results revealed that TVET institutions did not consider PPPs as a strategy for sustainable skills development for employability. Also established was policy inconsistency at the government level which hampers possibilities of partnerships in skills development. The results further show that industry plays an important role in skills development through internship, traineeship, and on-the-job education and training. The study recommended government through the relevant ministry and agents expedite the PPPs policy framework to include skills development as a standalone component. There is a need for government to incentivise private sector players to have PPPs in sustainable skills development for increased return on investment and subsequently economic growth.